Implementasi Kebijakan Pemerintah Daerah Terkait Retribusi dalam Meningkatkan Pendapatan Asli Daerah (Studi Kasus di UPTD Pengelola Prasarana Teknis Perhubungan Provinsi NTT Wilayah-1) - Danting, Maria Deonensia Melisitta; Toda, Hendrik; Benyamin, Rouwland A.; Long, Belandina (Innovative: Journal Of Social Science Research, 2025)
This study aims to describe and analyze the implementation of policies at the Technical Infrastructure Management Unit of Transportation of NTT Province- Region 1 in carrying out local government policies related to user fees in supporting Regional Original Revenue (PAD). This research uses a qualitative descriptive approach using four indicators of policy implementation, namely communication, resources, disposition, and bureaucratic structure. The results showed that the implementation of the program was carried out with limitations in terms of the availability of personnel and also the budget, but it was considered inefficient because of the small nominal in addition to cost cuts/budget efficiency and the lack of personnel because it covered two terminals. Another obstacle is the attitude of the community who are still reluctant to pay the mandatory retribution and still use shadow terminals. In conclusion, although there are still some obstacles, this program has been implemented in accordance with the applicable SOP provisions.